Sistem Informasi Bantuan Wira Usaha Baru (WUB) Pada Dinas Nakertrans Kabupaten Gorontalo - Sagga, Hairun Nissa; Latief, Mukhlisulfatih; Tuloli, Moh.Syafri (Diffusion: Journal of Systems and Information Technology, 2023)
The Manpower and Transmigration Service currently has a very difficult time monitoring the development of business assistance in each sub-district in Gorontalo district. This study aims to build a WUB assistance information system  using web GIS at the Nakertrans Office of Gorontalo Regency in order to assist in monitoring the development of business assistance. The method used is the prototype method where the stages are listening to customers, building / repairing the prototype, and the customer testing the prototype. This study resulted in an information system managing WUB assistance data based on a web GIS where this system has passed the test using blackbox and whitebox. The results of the test can be seen at which points are given assistance by using a web GIS or mapping where the system can see the places where assistance is given even though it can update the progress of the assistance provided is still running or not.Keywords: GIS; Prototypes; Information Systems ; New Entrepreneur